Specific effects of five subtypes of childhood maltreatment on suicide behaviours in Chinese adolescents: the moderating effect of sex and residence - Chang Peng; Junhan Cheng; Fajuan Rong; Yan Wang; Yafei Tan; Yizhen Yu (Cambridge University Press, 2023)
Abstract Aims Although childhood maltreatment has been widely supported to be a robust predictor of suicide behaviours, the effects of different childhood maltreatment subtypes remain controversial and inconclusive. Moreover, whether the effects differ by sex in urban and rural adolescents is still unknown. This study aimed to quantify the associations between five subtypes of childhood maltreatment and different suicide behaviour involvement. Methods A multistage cluster sampling method was adopted from April to December 2021 for adolescents aged 12 to 18 across five representative provinces of China. The Childhood Trauma Questionnaire-Short Form was used to measure childhood maltreatment subtypes. Suicide behaviour involvement was classified as none group, suicide ideator, suicide planner and suicide attempter. Confounding variables include demographic characteristics, smoking, drinking alcohol, depression and anxiety. Results Among a total of 18,980 adolescents, 2021 (10.6%) were suicide ideator, 1595 (8.4%) were suicide planner and 1014 (5.3%) were suicide attempter. Rural females had the highest proportion of suicide ideator (13.8%) and suicide planner (11.5%). Multinomial logistic regression analysis indicated that five childhood maltreatment subtypes were independently associated with suicide behaviours, except for associations between sexual abuse and suicide ideator as well as suicide planner (p > 0.05). Moreover, these associations differ by sex and residence. After adjusted for interactions of different subtypes, structural equation model indicated that the direct effects of childhood maltreatment subtypes on suicide behaviours from high to low were emotional abuse (β = 0.363, p < 0.001), physical abuse (β = 0.100, p < 0.001) and sexual abuse (β = 0.033, p = 0.003), while the effects of physical neglect and emotional neglect were not significant (p > 0.05). Conclusions Five subtypes of childhood maltreatment have specific and non-equivalence associations with suicide behaviours. Emotional abuse may have the strongest effect, and sexual abuse have an acute effect on suicide behaviours. Suicide prevention programs for Chinese adolescents could focus on those who experienced emotional, physical and sexual abuse. Furthermore, strategies should be tailored by sex and residence, and rural females deserve more attention.